Transformation of Human Resource Job Description in the Digital Era: Case Study at PT Jatelindo Perkasa Abadi - Deaotna Rivany; Veithzal Rivai Zainal; Aziz Hakim (Green Publisher, 2025)
Digital transformation has significantly changed the roles and responsibilities of human resources (HR) in organizations. This research aims to describe the changes in Human Resource (HR) job descriptions from administrative roles to strategic roles in the digital era, with a case study at PT Jatelindo Perkasa Abadi. The method used is descriptive qualitative with internal data collection techniques and through interviews with HR staff. The results show that digital transformation encourages the transfer of manual tasks to be automated by technology, as well as an increase in the role of HR as a strategic partner in supporting business growth. These changes include functions in talent management, HR analytics, and organizational development.